Clinical Features, Magnetic Resonance Imaging, and Treatment Experience of 20 Patients with Lymphocytic Hypophysitis in a Single Center - Zhu, Qiang; Qian, Ke; Jia, Guijun; Lv, Gang; Wang, Jisheng; Zhong, Liyong; Yu, Shuqing (World neurosurgery, 2019)
Lymphocytic hypophysitis (LYH) is a rare autoimmune inflammatory disease of the pituitary gland. In this study, we aim to characterize LYH at presentation and focus on the management and prognosis of LYH. A retrospective study of patients with LYH was conducted between 2011 and 2018 at a single institute. The patients were included by pathologic conformation and strict exclusion criteria. Clinical profile, imaging, and management data were collected. Twenty patients with LYH (16 women and 4 men) were included. Ten patients were diagnosed histologically and the remaining 10 patients were confirmed clinically of exclusion criteria. The median age at diagnosis was 37 years (range, 16–58 years). Presenting symptoms were followed by polyuria/polydipsia (11, 55%), vision changes (10, 50%), headache (8, 40%), menstrual irregularities and amenorrhea (4, 20%), diplopia (1, 5%), or sexual dysfunction (1, 5%). Eight patients had partial anterior pituitary hormone dysfunction. The thyroid-stimulating hormone axis was most involved. Ten patients received transsphenoidal surgery, 5 patients experienced steroid pulse therapy, and observation was performed on 5 patients. Only 5 patients (25%) showed improvement of anterior pituitary dysfunction after initial management. Recovery of diabetes insipidus occurred in 2 patients (18%). The overall recurrence rate was 22.2%. Nonoperative treatment is a better option for most patients with LYH because it is effective and noninvasive. Surgery is recommended for definitive diagnosis, severe or rapid progression of neurologic impairment, and glucocorticoid insensitivity. Periodic follow-up is mandatory in a patient's long-term management.